Battling for Shared Culture Between Indonesia and Malaysia in The Social Media Era - Suhardjono, Liliek Adelina (Humaniora, 2012)
This is a research paper that takes as its central issue recent contestations and negotiations between Indonesia and Malaysia regarding certain forms of these countries? intangible cultural heritage. In recent years, there has been an increasing incident in relation with cultural conflicts that happens between these two neighboring countries. These cultural conflicts specifically referred to the traditional performance arts, which has been hereditarily bequeathed by their respective ancestors. Despite the facts that both countries shared the same cultural roots, each side seems has a tendency to despise each other whenever the subject of culture ownership is being brought: both claim for the same cultural rights. Questions on which side is more entitled to the rights became public fierce debates; and it wildly happened especially in the online world through the medium of social networking platform. This paper examines the phenomenon on how should the ownership of authenticity be placed. And since it happens in the modern societies which cannot be separated from their digital personas, the role of social media is inexorably also be addressed. It will link the two identities of the public who is initially mere the audience of the performance then transform into the owner of the cultural product in dispute. This essay begins by a major length discussion about the concept of authenticity in culture, along with the ownership of intangible heritage, the motivation for claiming authenticity, and the protection of cultural property. It will then go on to the topic of the major changes brought by social media in the modern society. Subsequently it will continue to the state of cultural conflict between Indonesia and Malaysia over ?stolen? cultural heritage.